SONS: The JCMT legacy survey of debris discs in the submillimetre. Issue 3 (6th June 2017) - Holland, Wayne S.; Matthews, Brenda C.; Kennedy, Grant M.; Greaves, Jane S.; Wyatt, Mark C.; Booth, Mark; Bastien, Pierre; Bryden, Geoff; Butner, Harold; Chen, Christine H.; Chrysostomou, Antonio; Davies, Claire L.; et al.
Abstract: Debris discs are evidence of the ongoing destructive collisions between planetesimals, and their presence around stars also suggests that planets exist in these systems. In this paper, we present submillimetre images of the thermal emission from debris discs that formed the SCUBA-2 Observations of Nearby Stars (SONS) survey, one of seven legacy surveys undertaken on the James Clerk Maxwell Telescope between 2012 and 2015. The overall results of the survey are presented in the form of 850 μm (and 450 μm, where possible) images and fluxes for the observed fields. Excess thermal emission, over that expected from the stellar photosphere, is detected around 49 stars out of the 100 observed fields. The discs are characterized in terms of their flux density, size (radial distribution of the dust) and derived dust properties from their spectral energy distributions. The results show discs over a range of sizes, typically 1–10 times the diameter of the Edgeworth–Kuiper Belt in our Solar system. The mass of a disc, for particles up to a few millimetres in size, is uniquely obtainable with submillimetre observations and this quantity is presented as a function of the host stars' age, showing a tentative decline in mass with age. Having doubled the number of imaged discs at submillimetre wavelengths from ground-based, single-dish telescope observations, one of the key legacy products from the SONS survey is to provide a comprehensive target list to observe at high angular resolution using submillimetre/millimetre interferometers (e.g. Atacama Large Millimeter Array, Smithsonian Millimeter Array).